Nomogram based on multimodal echocardiography for assessing the evolution of diabetic cardiomyopathy in diabetic patients with normal cardiac function - Liu, Yi; Lu, Hao; Zhang, Yan; Cai, Mengjie; Guo, Jia; Ruan, Xiaofen (Frontiers in Cardiovascular Medicine, 2022)
Background Diabetic cardiomyopathy (DCM) remains asymptomatic for many years until progression to asymptomatic left ventricular diastolic dysfunction (ALVDD), a subclinical cardiac abnormality present in early-stage DCM. Because LV function in patients with type 2 diabetes mellitus (T2DM) may be subtly altered long before the onset of ALVDD, quantitative assessment of the risk of progression to early-stage DCM in T2DM patients with normal hearts is critical for delaying or even reversing DCM. Objective This study aimed to establish a nomogram with the aid of DCM characteristics revealed by multimodal echocardiography to assess the likelihood of the progression to early-stage DCM in T2DM patients with normal cardiac function. Methods Of the 423 T2DM patients enrolled, 302 were included in the training cohort and 121 in the validation cohort. The clinical characteristics, biochemical data, and multimodal echocardiographic parameters were collected. In the training cohort, the screened correlates of ALVDD were utilized to develop a nomogram for estimating the risk coefficient for early-stage DCM. This model was validated both in the training and validation cohorts. Results ALVDD was independently correlated with the number of comorbidities [with one comorbidity: odds ratio (OR) = 3.009; with two comorbidities: OR = 4.026], HbA1c (OR = 1.773), myocardial blood flow (OR = 0.841), and global longitudinal strain (OR = 0.856) (all P < 0.05). They constituted a nomogram to visualize the likelihood of DCM development in T2DM patients with normal cardiac function. The model was validated to present strong discrimination and calibration, and obtained clinical net benefits both in the training and validation cohorts. Conclusion We constructed and validated a nomogram to estimate the likelihood of developing early-stage DCM in T2DM patients with normal cardiac function. The alteration of the nomogram-predicted risk coefficient is expected to be proposed as a therapeutic target to slow or stop DCM progression.